One-day prevalence of asymptomatic carriage of toxigenic and non-toxigenic Clostridioides difficile in 10 French hospitals. (November 2022) - Le Monnier, A.; Candela, T.; Mizrahi, A.; Bille, E.; Bourgeois-Nicolaos, N.; Cattoir, V.; Farfour, E.; Grall, I.; Lecointe, D.; Limelette, A.; Marcade, G.; Poilane, I.; et al.
Summary: Background: Asymptomatic faecal carriage of Clostridioides difficile has been widely evaluated, but its prevalence across a wide range of clinical departments and related risk factors are not well described. The objectives of the PORTADIFF study were to evaluate the prevalence and identifying risk factors leading to asymptomatic carriage of both toxigenic and non-toxigenic C. difficile . Methods: The PORTADIFF study was a 1-day prevalence study carried out in 10 different French hospitals. Adult patients, who agreed to participate, were included in this study and provided a fresh stool sample. C. difficile strains isolated from carriage were characterized by polymerase chain reaction (PCR) detection of tcdA, tcdB, cdtA and cdtB, and PCR ribotyping. Results: In total, 721 patients were included in this study. The median age was 73 years (range 18–101 years) and the male/female ratio was 1.06. C. difficile (either toxigenic or non-toxigenic strains) was isolated from 79 (11%) patients; 42 (5.8%) strains were toxigenic. The prevalence rates of asymptomatic carriage ranged from 5% on surgical wards to 19% on long-term care wards. The main risk factors associated with asymptomatic carriage were antibiotic treatment within the preceding 3 months (81.8% vs 53.7%; P <0.01), hospitalization within the preceding 2 months (55.8% vs 33%; P <0.01), cumulative duration of hospital stay before study inclusion (mean 50.1 vs 34.5 days; P <0.047), and hospitalization on a ward with high global incidence of C. difficile infection. Conclusion: Eleven percent of hospitalized patients were asymptomatic carriers of toxigenic or non-toxigenic C. difficile, and may constitute a potential reservoir of C. difficile strains.